PENGARUH PERSEPSI KEMUDAHAN DAN TINGKAT LAYANAN TERHADAP PENGGUNAAN DOMPET DIGITAL PADA PEDAGANG DI PASAR ATAS SAROLANGUN - Rini Wahyuni; Hansen Rusliani; Eri Nofriza (Yayasan Nusantara Hasana Berdikari, 2026)
The rapid development of digital technology has transformed the way people conduct transactions, making the use of digital wallets a popular payment alternative due to their convenience and efficiency. The purpose of this study was to determine whether perceptions of convenience and service level partially and simultaneously influence digital wallet use among merchants at Pasar Atas Sarolangun.. The research method used is quantitative with Multiple Linear Regression analysis as a data analysis technique with the help of SmartPLS software. The population in this study was 300 respondents, sample determination using the Slovin formula, so the sample in this study was 171 respondents and this research was conducted on Traders in the Upper Market of Sarolangun Regency. The results of the study indicate that the F test of the digital wallet usage variable can be influenced by the perceived ease of use (X1) and service level (X2) variables simultaneously. Partially, Perceived Ease has a significant effect on the use of digital wallets. Service Level has a significant effect on the use of digital wallets